Persepsi Petani terhadap Penggunaan Rice Transplanter di Subak Guama Kecamatan Marga, Kabupaten Tabanan - PUTRA, KETUT ADI WAHYU; ANGGRENI, I G A LIES; WINDIA, I WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.1, Juli 2022DO - 10.24843/JAA.2022.v11.i01.p22, 2022)
Farmers' Perceptions on the Use of Rice Transplanters in Subak Guama, Marga District, Tabanan Regency.  Farmers in Subak Guama are still planting rice manually with human labor. The shortage of rice planting workers began to occur in several rice production centers. Most rice lands can still be planted manually, but the completion is usually not on time. The use of rice transplanter has the potential to solve this problem. Farmers' perceptions of rice transplanter technology need to be known in advance so that the implementation of the rice transplanter program can be sustainable. This study aims to identify the perceptions of Subak Guama farmers in Marga District, Tabanan Regency on the use of transplanters. The analytical method used is descriptive qualitative. Based on the results of research and discussion, it can be concluded that most farmers agree with the use of rice transplanters with a percentage of 76.46 percent. Based on indicators of the nature of using rice transplanter technology, 77.18 percent of farmers agreed; based on indicators of target or rice transplanter users, 75.76 percent of farmers agreed; based on indicators of target attitudes or rice transplanter users, 75.67 percent of farmers agreed; and based on indicators of target or user behavior 76.78 percent of farmers agreed. attitude indicator or rice transplanter users was 75.67 percent included in the agree category and the target behavior indicator or rice transplanter users with 76.78 percent achievement fall into the agree category.